(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
One of the greatest challenges facing people in the process of becoming South Africans today is that of building a cohesive national identity out of diverse and competing national, cultural and ethnic aspirations and identities that were never imagined as belonging to a single nation-state. This challenge has been made worse by the fact that the advent of the post-apartheid dispensation came with liberal democratic values of diversity, tolerance and various forms of freedom such as those of choice, association and speech. All of these freedoms have brought about an impediment to the cultivation of the spirit of patriotism, common belonging and unity among the peoples meant to become South Africans. While a number of obstacles have been identified in the quest to develop a sense of common belonging among the peoples who occupy the cartographic space known as South Africa today, the question of knowledge production and its divisive role in the making of South Africa has not yet been comprehensively addressed. This gap needs to be addressed urgently with specific reference to the field of producing historical knowledge because the manner in which historical events and narratives are imagined and reconstructed in South Africa today has the potential to constrain and/or enhance common belonging. This article is a decolonial epistemic perspective on the production of historical knowledge in South Africa and it argues that a decolonised historical narrative can possibly lead to the emergence of a cohesive South African national identity.